Women's Equality and the COVID-19 Caregiving Crisis. Issue 2 (29th June 2022) - Htun, Mala
Abstract : The COVID-19 pandemic revealed, but did not create, the caregiving crisis in the United States: for most people, it was already a major ordeal to provide reproductive labor. The caregiving crisis was less visible before the pandemic because it was suffered unequally, in part due to the different positions of American women. Some women paid other women to do care work, women received differing sets of benefits from federal and state governments, and some women got far more support from their employers than did others. Pandemic-induced shocks, including the closure of K–12 schools and childcare centers, and reduced access to domestic workers and elder care workers, seemed to have triggered a closer alignment of perspectives and interests among diverse women. Although women's demands for support seem to have pushed the Biden administration to propose more expansive family policies, stereotypes and norms that marginalize care work and care workers within families and across the economy also need to change to achieve equality for women.